PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA TOKO SUMBER RIZKI CILACAP JAWA TENGAH - Solihin, Dede; Setiyawan, Yudi (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of price and service quality on customer satisfaction at Sumber Rizki Cilacap store, Central Java, partially or simultaneously. The research method used is quantitative. The population in this study is 19,300. The number of samples used was 100 respondents. The data sources in the study are primary data through surveys, interviews, and questionnaires and secondary data in the form of literature studies and documentation. The data collection method is by way of questionnaire while the data analysis method is by means of multiple linear regression.  The results of this study are (1) Partially there is a positive and significant influence between price and customer satisfaction at the Rizki Cilacap Source Store Central Java, this can be proven from the simple linear regression equation Y=3.260+0.654X1, Correlation value of 0.895. The value of the determination coefficient was 80.0%, and the value of t calculated was 19.824 > t table 1.984 with a significance of 0.000 < 0.05 (2) Partially there was a positive and significant influence between service quality and customer satisfaction at  Sumber Rizki Cilacap Store Central Java, this can be proven from the simple linear regression equation Y=3.246+0.538X2. The correlation value was 0.879. The value of the determination coefficient is 77.3%, and the value of t is calculated 18.255 > t table 1.984 with a significance of 0.000 < 0.05, (3) Simultaneously there is a positive and significant influence between price and service quality on customer satisfaction at  Sumber Rizki Cilacap Store Central Java, this can be proven from the multiple linear regression equation Y=2.707+0.430X1+0.200X2. The value of the determination coefficient was 81.3%. The correlation value was 0.902. As well as the F value calculated 210.536 > F table 3.09 with a significant level of 0.000 < 0.05.